Design, layout and typographic systems - Mota, Marcelo José da (2018)
This paper presents a reflection on typographic language, historical findings about the theme and about typographic systems, and their uses in the field of graphic design. Exploratory researches were undertaken in the literature body, revealing approaches to a systematic articulation of the typographic language, including the search for evidence on how the use of research tools can make a significant difference in supporting decision-making. The main contribution of this work is to serve as a guide for graphic design students and researchers, in order to connect the design practice of methodological concepts about typographic language and the systems it embodies, aiming at a better adaptation of the theoretical-practical discourse of such professionals.